Video game art reader. - Funk, Tiffany; Reed, Michael (Amherst College Press, 2017)
The inaugural issue of VGAR celebrates video game culture as inclusive and global. Opening with an interview with the art director of the first independent Cuban video game, Savior, while the following essays from art historians, literary theorists, game designers, artists, educators, museum curators, and programmers all engage with video games as an important part of the global art landscape. Each engages with what makes good game art with special attention to the transnational cadre of gamers that play them.